Regression of Left Ventricular Mass in Athletes Undergoing Complete Detraining Is Mediated by Decrease in Intracellular but Not Extracellular Compartments. (September 2019) - Swoboda, Peter P.; Garg, Pankaj; Levelt, Eylem; Broadbent, David A.; Zolfaghari-Nia, Ashkun; Foley, A. James R.; Fent, Graham J.; Chew, Pei G.; Brown, Louise A.; Saunderson, Christopher E.; Dall'Armellina, Erica; Greenwood, John P.; et al.
Abstract : Background: Athletic cardiac remodeling can occasionally be difficult to differentiate from pathological hypertrophy. Detraining is a commonly used diagnostic test to identify physiological hypertrophy, which can be diagnosed if hypertrophy regresses. We aimed to establish whether athletic cardiac remodeling assessed by cardiovascular magnetic resonance is mediated by changes in intracellular or extracellular compartments and whether this occurs by 1 or 3 months of detraining. Methods: Twenty-eight athletes about to embark on a period of forced detraining due to incidental limb bone fracture underwent clinical assessment, ECG, and contrast-enhanced cardiovascular magnetic resonance within a week of their injury and then 1 month and 3 months later. Results: After 1 month of detraining, there was reduction in left ventricular (LV) mass (130±28 to 121±25 g; P <0.0001), increase in native T1 (1225±30 to 1239±30 ms; P =0.02), and extracellular volume fraction (24.5±2.3% to 26.0±2.6%; P =0.0007) with no further changes by 3 months. The decrease in LV mass was mediated by a decrease in intracellular compartment volume (94±22 to 85±19 mL; P <0.0001) with no significant change in the extracellular compartment volume. High LV mass index, low native T1, and low extracellular volume fraction at baseline were all predictive of regression in LV mass in the first month. Conclusions: Regression of athletic LV hypertrophy can be detected after just 1 month of complete detraining and is mediated by a decrease in the intracellular myocardial compartment with no change in the extracellular compartment. Further studies are needed in athletes with overt and pathological hypertrophy to establish whether native T1 and extracellular volume fraction may complement electrocardiography, echocardiography, cardiopulmonary exercise testing, and genetic testing in predicting the outcome of detraining. Abstract : Supplemental Digital Content is available in the text.